Exploring the Use of Educational Material About Shoulder Dysfunction: A Quality Improvement Project in People With Amyotrophic Lateral Sclerosis. (May 2018) - Burke, Katherine; Ellrodt, Amy Swartz; Levine, Jason; Adams, Taylor; Allis, Rebecca; Macmurdie, Ian; Paganoni, Sabrina
Abstract : Abstract: Shoulder pain is a common secondary complication of amyotrophic lateral sclerosis (ALS) that can contribute to functional decline and decreased participation in daily activities. The purpose of this study was to assess the effectiveness of an educational brochure aimed at improving knowledge regarding shoulder pain and dysfunction in people with ALS. Participants completed a preintervention survey with questions regarding their knowledge of how ALS may affect their shoulders. After completing the presurvey, they were mailed a brochure that described shoulder health and range of motion and stretching exercises. Four weeks after receiving the brochure, participants were then asked to determine the effectiveness of the educational materials in terms of impact on shoulder-related knowledge and self-efficacy with regard to prevention of shoulder pain and dysfunction. More than 50% of participants reported pain, decreased range of motion, or weakness in at least one shoulder since being diagnosed with ALS. All participants were interested in receiving educational materials, and all agreed that the brochure was easy to interpret and understand, with most (87%) reporting that it was helpful. Educational brochures are one strategy to improve awareness about shoulder health and to educate patients with ALS about exercises that may help reduce shoulder pain and dysfunction. Abstract : Supplemental digital content is available in the text.